Addition of mechanically processed cellulosic fibers to ionomer cement: mechanical properties - Rafael Menezes SILVA; Vinícius Xavier Mattar de CARVALHO; Vitor César DUMONT; Maria Helena SANTOS; Ana Márcia Macedo Ladeira CARVALHO (Sociedade Brasileira de Pesquisa Odontológica, 2015)
In this study, conventional restorative glass ionomer cement (GIC) was modified by embedding it with mechanically processed cellulose fibers. Two concentrations of fibers were weighed and agglutinated into the GIC during manipulation, yielding Experimental Groups 2 (G2; 3.62 wt% of fibers) and 3 (G3; 7.24 wt% of fibers), which were compared against a control group containing no fibers (G1). The compressive strengths and elastic modulus of the three groups, and their diametral tensile strengths and stiffness, were evaluated on a universal test machine. The compressive and diametral tensile strengths were significantly higher in G3 than in G1. Statistically significant differences in elastic modulus were also found between G2 and G1 and between G2 and G3, whereas the stiffness significantly differed between G1 and G2. The materials were then characterized by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). Heterogeneously shaped particles were found on the G2 and G3 surfaces, and the cement matrices were randomly interspersed with long intermingled fibers. The EDS spectra of the composites revealed the elemental compositions of the precursor materials. The physically processed cellulosic fibers (especially at the higher concentration) increased the compressive and diametral tensile strengths of the GIC, and demonstrated acceptable elastic modulus and stiffness.